When traditional meets modern : second demographic transition theory and the indicators of family change. - Tan, Patricia Shi Nan. (2010)
In the West, the fundamental changes in family formation and fertility in industrialized societies after the 1960s were revolutionary. Theorists of the Second Demographic Transition (SDT) postulated that value change towards individualism has been the reason generating the shifts in fertility behavior and family formation. Similar demographic shift is also experienced in East Asia whereby the most prominent shift includes delayed marriages, the reduction in marital fertility and non-marriages. This research study explores the value orientation toward marriage plans, marital living arrangement and fertility desires among Singaporean Chinese graduates; and the extent to which the SDT theory holds in this context. It was found that despite similar trends of individual autonomy and self fulfillment postulated by the SDT theory, there was also aspects of collective interest and happiness when the indicators of family change are broaden to, for example, include the marriage tradition of the wedding banquet. This study further highlight the role of multiple agents that include the bride, the bride’s parents and the commercial sector’s contribution, that explain why the traditional familial value of collectivism persisted. Theoretically, this study suggests that traditional and contemporary values coexist and suggest how future research can include specific dimensions of familial behaviors when employing the SDT theory to better conclude individual value orientation.